Does waterfall aerosol influence mucosal immunity and chronic stress? A randomized controlled clinical trial. Issue 1 (December 2017) - Grafetstätter, Carina; Gaisberger, Martin; Prossegger, Johanna; Ritter, Markus; Kolarž, Predrag; Pichler, Christina; Thalhamer, Josef; Hartl, Arnulf
Abstract Background The specific microclimate of alpine waterfalls with high levels of ionized water aerosols has been suggested to trigger beneficial immunological and psychological effects. In the present three-armed randomized controlled clinical study, we focused on effects on (i) immunological reagibility, on (ii) physiological stress responses, and on (iii) stress-related psychological parameters. Methods People with moderate to high stress levels (n = 65) spent an active sojourn with daily hiking tours in the National Park Hohe Tauern (Großkirchheim, Austria). Half of the group was exposed to water aerosol of an alpine waterfall for 1 h/day (first arm, n = 33), whereas the other half spent the same time at a distant site (second arm, n = 32). A third arm (control, n = 26) had no intervention (except vaccination) and stayed at home, maintaining their usual lifestyle. The effect of the interventions on the immune system was tested by oral vaccination with an approved cholera vaccine and measuring specific salivary IgA antibody titers. Lung function was determined by peak expiratory flow measurement. Electric skin conductance, heart rate, and adaption of respiration rate were assessed as physiological stress parameters. Psychological stress-related parameters were analyzed by questionnaires and scales. Results Compared to the control group, both intervention groups showed improvement of the lung function and of most physiological stress test parameters. Analysis of the mucosal immune response revealed a waterfall-specific beneficial effect with elevated IgA titers in the waterfall group. In line with these results, exposure to waterfall revealed an additional benefit concerning psychological parameters such as subjective stress perception (measured via visual analog scale), the Global Severity Index (GSI), and the Positive Symptom Total (PST). Conclusions Our study provides new data, which strongly support an "added value" of exposure to waterfall microclimate when combined with a therapeutic sojourn at high altitude including regular physical activity.